(untitled) (Docentes 2.0 Journal, 2021)
When reflecting on the term literacy, individuals immediately imagine a subject without minimum literacy skills. This article was conceived to study the importance of generating knowledge in the 21st century. It arose from the antagonism that experts should only publish scientific publications. For the study’s undertaking, a multidisciplinary approach was maintained, where different perspectives were incorporated and conceptions about Social Sciences, psychology, citizen, social and pedagogical participation. Qualitative research of the phenomenological-hermeneutic method was carried out. Ten (10) social actors of the International Workshop of Writing Scientific Articles were interviewed to structure, codify, and categorize the results. This epistemic journey allowed a theoretical approach focused on the literacy of social actors to generate knowledge through meaningful science education. Based on the social actors’ voice, it was established the tearing of each editorial’s bureaucratic chains because the experience is more accessible in the digital era. However, illiteracy has spread rapidly, incited by the old school groups, creating confusion in the events, and expanding their hegemony. Therefore, scientific literacy (SLC) is not only focused on the common factor of scientific activity of how, but also the strengthening of science through Higher Education Institutions, research groups, organizations, and educational enterprises.